Reliability assessment of island multi‐energy microgrids - Marcos Santos (Energy Conversion and Economics, 2021)
Abstract Multi‐energy microgrids could result in more flexibility and increase reliability by interconnecting networks. Electricity and gas networks exhibit very different dynamic behaviours in response to a fault or failure. Gas networks have built‐in energy storages that can continue to provide a reliable supply if gas inputs to the system are compromised. This study presents a novel reliability assessment method applied to multi‐energy microgrids; the method combines an incidence matrix analysis that identifies the connectivity between sources and load points with a sequential Monte Carlo simulation and generation adequacy evaluation. A case study is conducted by using an electricity‐gas microgrid. The electricity network is a multi‐sourced grid, whereas the gas network is supplied by a biogas plant. The linepack (gas stored along the pipelines) is modelled to account for the slower gas dynamics. The proposed method is evaluated on a real‐world electricity distribution network in Austria. The results indicate the reliability benefits of forming a multi‐energy microgrid.